TINGKAT PENERAPAN HASIL PENDIDIKAN DAN PELATIHAN MANAJEMEN DAN KEPEMIMPINAN BP3K BAGI PIMPINAN BP3K - Adi Widiyanto; Toni Nugraha (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Level of Implementation of Training result of The Training BP3K Management and Leadership For BP3K Leaders. This research is an evaluation to know the level of application of training materials by training partisipants to subject matters that have been trained in Management Training and Leadership of BP3K For BP3K Leaders. This research uses descriptive method with quantitative approach and supported qualitative.Data collection by survey technique. To strengthen the results, the data were also collected from the assessment of the direct superior of the training participants and the co-workers of the training participants. The results of this study indicate that the level of application of the material for the overall training subject matters that has been trained on average included in the category is very high. But there is material for Training Subject Matter BP3K Organizing Activity results of its application level not yet optimal, although still in high category. This is because decision-making on the aspect of organizing activities wholly depends on policies at the higher levels of Institutions.